(untitled) (Research, Society and Development, 2022)
Chronic non-communicable diseases (NCDs), are a public health problem and are associated with about 54.7% of deaths in Brazil in 2019. The World Health Organization (WHO) plan aims at the global reduction of Chronic noncommunicable diseases through strategies that promote the improvement of the population’s lifestyle. Among the diseases with the highest morbidity and mortality rates are, circulatory system diseases, cancers, chronic respiratory diseases, and Diabetes Mellitus. Aiming to add one more strategy in the fight against Chronic noncommunicable diseases and their better control, the objective of this study is to elaborate a model (prototype) of an application for the prevention and control of Chronic noncommunicable diseases that helps in health education for the control and reduction of their incidence. This is a descriptive study, of the experimental development of an application called Previne+, through a qualitative approach, with a research and action procedure. The application’s content is focused on prevention, health monitoring, risk scores for chronic diseases, healthy living alarms and user habit profiles. It is considered the relevance of the use of technology as a support and control in reducing the aggravations of Chronic noncommunicable diseases and, in the near future, as another strategy to reinforce the results expected by the WHO in relation to improving the quality of life of patients with Chronic noncommunicable diseases.